(untitled) (REMUNOM, 2025)
Spent Pot Lining (SPL), a hazardous waste generated during the Hall-Héroult process, amounts to 1.4–1.8 million tonnes annually, with China accounting for nearly 60% of global production. Rich in fluorides, cyanides, and reactive metals, SPL poses serious environmental risks, including soil and groundwater contamination and toxic gas emissions. Traditional disposal methods such as landfilling and encapsulation are increasingly unsustainable, prompting the development of advanced thermal, hydrometallurgical, and integrated treatment technologies. These approaches enable the recovery of valuable products, such as fluoride salts, alumina, and carbon, while reducing hazardous residues. Additionally, cement co-processing has emerged as a practical large-scale solution, achieving both neutralization of toxic compounds and energy recovery. Industrial case studies from China, Norway, and Brazil demonstrate >95% landfill diversion, proving the technical feasibility of circular SPL management. However, challenges remain, including high CAPEX, regulatory inconsistencies, and SPL heterogeneity. Future progress depends on the harmonization of international policies, the advancement of clean technologies, and the creation of sustainable supply chains to achieve zero-waste, carbon-neutral aluminium production.